Miracle seeds: Biased expectations, complementary input use, and the dynamics of smallholder technology adoption - Miehe, Caroline; Nabwire, Leocardia; Sparrow, Robert; Spielman, David J.; Van Campenhout, Bjorn (University of Chicago Press, 2025)
To fully beneﬁt from new agricultural technologies like improved seed varieties, signiﬁcant investment in complementary inputs such as fertilizers and pesticides, and practices such as systematic planting, irrigation, and weeding are also required. Farmers may fail to recognize the importance of these complements, leading to disappointing crop yields and outputs and, eventually, dis-adoption of the improved variety. Using a ﬁeld experiment, we test an information intervention among smallholder maize farmers in eastern Uganda that points out these complementarities. We ﬁnd that farmers adopt less after they have been sensitized about the need to use complementary inputs to unlock the adoption premium. We rationalize this ﬁnding with a simple theoretical model where farmers have mis-speciﬁed mental models of the technology production function and conclude that most farmers in our sample do indeed believe in miracle seeds.